In search of a docking protocol to distinguish between DNA intercalators and groove binders: genetic algorithm vs. shape-complementarity based docking methods. Issue 88 (25th September 2015) - al-Rashida, Mariya; Ahsen, Sana
<x xml:space="preserve">Abstract</x> A comparison of docking of DNA groove binders and intercalators using genetic algorithm and shape-complementarity based methods is presented.